Hereditas - Massoumi, Ramin; Baumgartner, Stefan; Shi, Yongyong; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Hereditas publishes original cutting-edge research and reviews. As the Official journal of the Mendelian Society of Lund, the journal welcomes research from across all areas of human, plant, animal and microbial genetics and epigenetics. Topics of interest also include cancer genetics, cancer biology, non-coding RNA, Data Mining, and Genome Technology.
Keywords: Genetics; Evolution (Biology).; Genetics and Genomics; Evolutionary Biology